2015
DOI: 10.1016/j.cell.2015.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Bacteria from the Gut Microbiota Regulate Host Serotonin Biosynthesis

Abstract: Cell 161, 264-276; April 9, 2015) In Figure S5D of this article, the representative flow cytometry plot of forward versus side scatter for unstimulated platelets was incorrectly duplicated during the final formatting of the paper for SPF+PCPA and GF conditions. The figure has been corrected online, and the originally published descriptions of the results in the text and figure legend are accurate.In Figure 3A, the ''GF+conv'' bar represents germ-free (GF) mice conventionalized with standard pathogen-free (SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
497
7
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(537 citation statements)
references
References 0 publications
20
497
7
13
Order By: Relevance
“…The same researchers posit that hydrogen sulfide production can modulate gut mobility through interactions with vanilloid receptors found in capsaicin-sensitive nerve fibres 25. In a different study, it was demonstrated that gut microbes were able to communicate with the brain and influence the central nervous system by directly altering neurotransmitter levels 26. As an example, the human gastrointestinal tract contains most of the body’s serotonin (5-hydroxytryptamine (5-HT)) 26…”
Section: Biochemical Signalling From the Gastrointestinal Tract To Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The same researchers posit that hydrogen sulfide production can modulate gut mobility through interactions with vanilloid receptors found in capsaicin-sensitive nerve fibres 25. In a different study, it was demonstrated that gut microbes were able to communicate with the brain and influence the central nervous system by directly altering neurotransmitter levels 26. As an example, the human gastrointestinal tract contains most of the body’s serotonin (5-hydroxytryptamine (5-HT)) 26…”
Section: Biochemical Signalling From the Gastrointestinal Tract To Thmentioning
confidence: 99%
“…The aim of a recent study was to demonstrate that the microbiota directly regulates 5-HT via metabolic signalling 26. The authors found out that introduction of spore-forming bacteria into the gut leads to the breakdown of short-chain fatty acids and reduced serotonin production; decreased serotonin levels in the gut then trigger neurochemical signalling to both the brain and the central nervous system.…”
Section: Biochemical Signalling From the Gastrointestinal Tract To Thmentioning
confidence: 99%
“…and Lactobacillus from colons of formula fed piglets [9]. Interestingly, Yano et al reported that gut microbiota regulate host sertotonin biosythesis [10]. Several exogenous factors including specific dietary components and microbiota alter serotonin release [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in healthy individuals, the gut microbiota has been shown to facilitate the metabolism of tryptophan by enteroendocrine cells into its metabolites, kynurenine and serotonin (5). This process may occur via SCFAs increasing tryptophan hydroxylase expression (1).…”
mentioning
confidence: 99%
“…This process may occur via SCFAs increasing tryptophan hydroxylase expression (1). However, other microbiota metabolites may be involved, and there is also evidence of de novo production of serotonin by bacteria, at least in culture (5). Of interest, germ-free mice have been shown to have higher levels of tryptophan and lower levels of serotonin when compared to control mice, suggesting impaired conversion in this population.…”
mentioning
confidence: 99%